2015
DOI: 10.1002/cyto.b.21330
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood regulatoryTcell levels are correlated with some poor prognostic markers in newly diagnosed lymphoma patients

Abstract: Background: Regulatory T cells (Tregs) are a specialized subpopulation of CD41 T cells which maintain the immune system homeostasis. They may increase during cancer progression and have been correlated with a worse prognosis in many malignancies. However, the role of Treg cells in lymphoma is debated.Methods: In this study, we assessed the peripheral blood levels of CD41 CD251 FOXP31 Tregs in newly diagnosed patients with lymphoma and tried to find a relationship with patient characteristics. Twenty one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
11
2
Order By: Relevance
“…Thus far, published data on the levels of circulating Treg cells in newly diagnosed patients with NHL have yielded conflicting results. While some studies reported that the pre-therapy levels of Treg cells in patients with B-cell NHL are higher in PB compared with those of healthy individuals, other studies reported the opposite, or no association (12)(13)(14)(15)(16)(17). In the present study, the levels of circulating Treg cells tended to be lower in patients compared with healthy controls prior to the initiation of rituximab-based treatment, but their levels were markedly increased after CR.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Thus far, published data on the levels of circulating Treg cells in newly diagnosed patients with NHL have yielded conflicting results. While some studies reported that the pre-therapy levels of Treg cells in patients with B-cell NHL are higher in PB compared with those of healthy individuals, other studies reported the opposite, or no association (12)(13)(14)(15)(16)(17). In the present study, the levels of circulating Treg cells tended to be lower in patients compared with healthy controls prior to the initiation of rituximab-based treatment, but their levels were markedly increased after CR.…”
Section: Discussioncontrasting
confidence: 63%
“…One of the objectives of the present study was to evaluate the interrelationships among the regulatory cell subsets, as these cells are known to interact with each other to establish a potent immunoregulatory environment to control tumor growth. Associations among circulating regulatory cell subsets and standard disease markers in patients with B-cell NHL has been evaluated by few studies with conflicting results (12)(13)(14)(15)(16)(17)20). The findings of the present study revealed that the levels of circulating Treg cells were not significantly correlated with Breg or iNKT cells, either pre-or post-rituximab-based therapy.…”
Section: Discussioncontrasting
confidence: 61%
“…43 The manipulation of these suppressor cells has become the focus of attention as Tregs are significantly increased in peripheral blood of NHL patients receiving or not chemotherapy 44 and have been associated with a poor prognosis. 26 Different strategies have been developed to reduce the toxic side effects of IL-2 and its capacity to activate negative immune regulators. The generation of IL-2 variants able to expand preferentially immune effector cells has been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The above-studied cohorts were similar (Europeans,~60 years), however direct comparison of the results cannot be totally correct due to variations in applied methodology: (1) calculation of Treg percentages in total population of PBMCs [100] or blood cells [99]; and (2) different definition of Treg phenotypes. Some studies on lymphoma patients have similarly found no variation in Treg levels in comparison to healthy volunteers [101,102], while others reported several-fold difference regardless of nationality, age and disease status (newly diagnosed vs. relapsed) [102][103][104].…”
Section: Treg Subsets May Be Overrepresented In Peripheral Blood Of Pmentioning
confidence: 99%